Economic Independence of Islamic Boarding Schools - Mi'raj, Denizar Abdurrahman; Zaki, Irham; Hasib, Fatin Fadhilah (Univeristas Islam Bandung, 2023)
Historically, Islamic boarding schools or pesantren have contributed greatly to the advancement of Islamic civilization in Indonesia. In addition to its function in the field of education, pesantren also have an important role in empowering the economy of the people. The independence of the pesantren can be applied to provide motivation and encouragement to students to become established in the economic field. This study uses a qualitative approach with a case study method. The purpose of this study is to describe the form of economic independence of pesantren using a case study at Riyadlul Jannah Islamic boarding school, Pacet. A pesantren that has a strong vision and mission in the fields of economy and empowerment. The finding of this research is that pesantren provide intensive education and instil an entrepreneurial spirit to the students, even brainwashing about the importance of entrepreneurship is given. The independence that is carried out is also not fixed on theory alone, but also in direct application to the various business units owned by the Islamic boarding school. Some of the business units owned by the Islamic boarding schools are restaurants, agriculture and fisheries, printing, mineral water production, and tours & travel.